2011
DOI: 10.1039/c0md00154f
|View full text |Cite
|
Sign up to set email alerts
|

Increase in plasma ceramide levels via secretory sphingomyelinase activity in streptozotocin-induced diabetic rats

Abstract: Ceramide mediates apoptosis and is upregulated by oxidative stress. To reveal the causative agent of diabetes-induced complications, we examined the changes in ceramide metabolism during diabetes. Two and 8 weeks after intraperitoneal injection of streptozotocin (STZ: 40 mg kg À1 body weight) to rats, tissue ceramide levels were analyzed by liquid chromatography-electrospray tandem mass spectrometry (LC-MS/MS). Blood glucose was significantly increased 2 weeks after STZ administration. Alanine aminotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Similar results were obtained in diabetic rats. 17) These observations suggested that aging did not affect hepatic ceramide metabolism.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Similar results were obtained in diabetic rats. 17) These observations suggested that aging did not affect hepatic ceramide metabolism.…”
Section: Discussionmentioning
confidence: 66%
“…Excessive cholesterol intake increased plasma ceramides in apolipoprotein E knockout mice (apoE −/− ), a typical animal model for atherosclerosis. 16) In addition, we previously reported that the increase in plasma ceramide level was caused by increased activity of sSMase in the streptozotocin-induced diabetic rats, 17) thus suggesting that the elevation of plasma ceramide was an important factor in atherogenesis. sSMase activity also increased in response to stimulation of macrophages obtained from patients with chronic heart failure 18) and type 2 diabetes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we demonstrated that increased sSMase activity resulted in an increase of the ceramide in the plasma of diabetic and atherosclerotic murine models which had been exposed to systemic oxidative stress (17,18). These results suggest that inhibition of sSMase activity is effective in the prevention of these diseases.…”
mentioning
confidence: 80%
“…Change in sSMase activity by the redox state. sSMase activities were measured using NBD C 6-SM as a substrate, as previously described (17,18). To examine the effect of oxidation on sSMase activity, 100 mL of rat plasma was incubated with 500 mL of H2O2 solution at 0, 10, 100, and 1,000 mm final concentrations for 15 min at 37˚C in 20 mm Tris-HCl buffer (pH 7.5) (the oxidized sample).…”
Section: Methodsmentioning
confidence: 99%